2019
DOI: 10.1111/ger.12437
|View full text |Cite
|
Sign up to set email alerts
|

Development of an instrument to assess oral hygiene ability in older adults: The oral hygiene ability instrument

Abstract: Objectives To describe the development process of an instrument to assess the ability to manage daily oral hygiene and the cause of impaired oral hygiene. The instrument is initially aimed for use by the dental team in the ageing population. Background Oral hygiene is an important component of oral health. Inability to manage oral hygiene combined with other risk factors often results in poor oral health and impaired quality of life. Methods A guideline for instrument development was used during the constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In previous research it was concluded that it was crucial to integrate the older adults' preferences and values regarding their oral health in oral assessments (34). Inspired by OHAI (53) to assess ability during the oral hygiene task in home settings, new opportunities for learning were opened. For example, the results show that older adults were recommended to use a chair in the bathroom when balance was poor.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research it was concluded that it was crucial to integrate the older adults' preferences and values regarding their oral health in oral assessments (34). Inspired by OHAI (53) to assess ability during the oral hygiene task in home settings, new opportunities for learning were opened. For example, the results show that older adults were recommended to use a chair in the bathroom when balance was poor.…”
Section: Discussionmentioning
confidence: 99%
“…For the intra‐ and inter‐rater reliability of parts II (clinical examination) and III (observation of ADL‐oral hygiene), four dental professionals (one dental hygienist, one dentist, two dental nurses working with dental prophylaxis) participated. The raters were the same as those who conducted all examinations during the development and first evaluation of the OHAI 13 . The group of dental professionals all had extensive experience working in dentistry (30–40 years) and working with older patients (≥20 years).…”
Section: Methodsmentioning
confidence: 99%
“…A new instrument, the Oral Hygiene Ability Instrument (OHAI), was developed mainly based on the factors described in the qualitative study 12,13 . The OHAI is intended to be used in prophylactic work to assess the cause of any inability for older adults to manage oral hygiene self‐care.…”
Section: Introductionmentioning
confidence: 99%
“…-OHAI (48), for measuring ability to perform oral hygiene tasks. The OHAI should be used when indicated, when ROAG (47) shows 2 or 3 at the variables 'teeth', 'gum', 'saliva' and 'oral mucosa' or if the older adult expresses concerns about difficulties with maintaining oral hygiene.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…It was also included to provide a common language. When ROAG indicated difficulties regarding oral hygiene (= score 2 or 3 on 'teeth' or 'gum' within ROAG), the ability to perform oral hygiene tasks could be explored inspired by the Oral Hygiene Ability Instrument (OHAI) (48).…”
Section: IImentioning
confidence: 99%